2019
DOI: 10.1136/heartjnl-2019-315437
|View full text |Cite
|
Sign up to set email alerts
|

Predicting sudden cardiac death in a general population using an electrocardiographic risk score

Abstract: ObjectiveWe investigated whether combining several ECG abnormalities would identify general population subjects with a high sudden cardiac death (SCD) risk.MethodsIn a sample of 6830 participants (mean age 51.2±13.9 years; 45.5% male) in the Mini-Finland Health Survey, a general population cohort representative of the Finnish adults aged ≥30 years conducted in 1978–1980, we examined their ECGs, following subjects for 24.3±10.4 years. We analysed the association between individual ECG abnormalities and 10-year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 30 publications
1
39
0
4
Order By: Relevance
“…9,22,25 Therefore, the combination of several ECG criteria seems to be a better approach, as shown in the case of sudden cardiac death, where an ECG score consisting of 5 ECG criteria significantly improved risk prediction compared with single ECG parameters. 26 The Daniel-ECG-score, 19 the only ECG score devised so far for the diagnosis of acPE, did not produce convincing results. The very good overall diagnostic value of our nECGs in the estimation of acPE pretest probability can be due to the carefully selected ECG criteria, which best reflect the most important pathogenetic components of acPE.…”
Section: Discussionmentioning
confidence: 94%
“…9,22,25 Therefore, the combination of several ECG criteria seems to be a better approach, as shown in the case of sudden cardiac death, where an ECG score consisting of 5 ECG criteria significantly improved risk prediction compared with single ECG parameters. 26 The Daniel-ECG-score, 19 the only ECG score devised so far for the diagnosis of acPE, did not produce convincing results. The very good overall diagnostic value of our nECGs in the estimation of acPE pretest probability can be due to the carefully selected ECG criteria, which best reflect the most important pathogenetic components of acPE.…”
Section: Discussionmentioning
confidence: 94%
“…Then, a cumulative ECG risk score was applied to the remaining 1377 ECGs, in order to identify subjects with a high SCD risk. This score specifically predicts SCD risk relying on the presence of ≥3 specific ECG alterations: heart rate > 80 beats per minute (bpm), PR interval > 220 ms, QRS duration > 110 ms, left ventricular hypertrophy, and T wave inversion [3]. The score has recently been developed by a Finnish research group who demonstrated as among 6830 Mini-Finland Health Survey participants the risk for SCD progressively increased with each additional ECG abnormality, whereby subjects with ≥3 ECG abnormalities exhibited the highest risk [Hazard Ratio (HR) = 10.23; 95% CI 5.29-19.80; p < 0.001] for SCD.…”
Section: Ecg Risk Scorementioning
confidence: 99%
“…Conversely, approximately 50% of all deaths occur in patients without a prior diagnosis of heart disease who did not meet low Left Ventricular Ejection Fraction (LVEF) criteria, which occupies a central position in current guidelines for prophylactic Implantable Cardioverter-Defibrillators (ICD) implantation [2]. Therefore, some combinations of arrhythmic risk markers beyond LVEF have been proposed and the recent Finnish Electrocardiogram (ECG) score [3], based on specific ECG alterations, successfully identifies general population subjects with a high SCD risk. This study set out to elucidate the relationship between the presence of the ECG abnormalities associated with progressively increasing risk for SCD and several other clinical parameters in order to provide new potential risk stratification tools.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no simple method for identifying apparently healthy people who have a high risk of SCD. Based on ECG and outcome data in 6830 subjects in the Mini-Finland Health Study, Holkeri and colleagues1 identified five simple abnormalities on a baseline ECG that were independently associated with SCD risk: heart rate >80 beats/min, PR duration >220 ms, QRS duration >110 ms, left ventricular hypertrophy and T-wave inversion. In a separate validation cohort of 10 617 subjects, the presence of 1, 2 or 3 of these abnormalities was associated with a progressive increase in SCD risk with an HR of 10.82 (95% CI 3.23 to 36.25) for patients with 3 of more of these ECG findings compared with those with no ECG abnormalities (figure 1).…”
mentioning
confidence: 99%